Knowing me, knowing you: A comparative study on the effects of anonymous and conference peer feedback on the writing of learners of English as an additional language. (December 2020) - Zaccaron, Rafael; Xhafaj, Donesca Cristina Puntel
Abstract: This study compares the effectiveness and perception of anonymous and conference peer feedback on the writing of learners of English as an Additional Language (EAL). The 24 participants attended two classes of EAL at upper-intermediate level in an extension project at a university in Brazil. Both groups were experimental. One engaged with asynchronous peer feedback via email only, and the other also had a peer conference (face-to-face interaction). Data, collected over one semester, encompassed first drafts, peer feedback, and revised drafts of an argumentative essay along with responses to a questionnaire. The results showed that both types of feedback were effective to a similar extent. While peer conferences were seen as an opportunity for learners to clarify outstanding feedback issues, they did arouse some hostility. Deindividuation, the feeling individuals have when in groups, seemed to foster more feedback among anonymous reviewers. In addition, the study contributes to the field by reporting that learners seem to pay more attention to peer feedback than to teacher feedback because of the uncertainty it generates, which might enhance noticing. Pedagogical implications of the findings are discussed focussing on writing developed in general EAL courses. Highlights: Anonymous and conference peer feedback serve different purposes. Anonymity fostered uptake of comments through deindividuation. Peer conference was the locus for clarification but also led to some hostility. Less than 5% of invalid peer feedback led to errors in uptake. Lack of confidence in peer feedback made writers more attentive and critical.